A hybrid active queue management technique for QoS based unicasting protocols in MANETs - Mahapatro, Susrita; Kumar sahu, Prabhat; Kumar Dash, Pradeep (International Journal of Engineering and Technology, 2018)
Mobile Ad hoc Networks (MANETs) is the interconnection of several self-energy dependent mobile nodes. It is one of the self-configured and infrastructure less network. In MANET the issues are security, Quality Of Services, Congestion etc. The major issue of MANET is to control the congestion. Congestion means the network capacity is larger than the no of packets transmitted across the network.Â  In this paper, an effort has been made to evaluate and analyze the performance of the network by means of comparing two on-demand reactive routing protocols such as AODV [Ad-hoc On-demand Distance Vector] and DSR [Dynamic Source Routing] with each other along with also by comparing with DSDV [Destination Sequenced Distance Vector], which is a proactive routing protocol. The comparison is also being made under the light of two queue management techniques such as RED (Random Early Detection) and Droptail. A gateway discovery algorithm is being used by both AODV and DSR routing protocols, which uses the mechanism of connecting mobile nodes through gateway, however Bellman-Ford algorithm is being used by DSDV which uses the concept of including freedom from loops in the routing table. By means of simulation through NS-2 network simulator by varying the number of nodes, we observe that the performance differentials of AODV, DSR, and DSDV routing protocols are directed to foremost performance differentials to guarantee QoS for both of these protocols in RED and Droptail queue management techniques. There is a lot of queue management approach to minimize the congestion rate and transfer the data successfully to the destination. Two queue management techniques popularly used to manage queues in MANets are Active queue management and Passive queue management. Active queue management is widely used and RED is the most popular approach which gives low average delay, high throughput and lower packet drop rate. But RED algorithms have some drawback. So here we are using a hybrid approach, named as MRED by means of combining the features of both RED and ECN to overcome the drawbacks of RED.